Murine Pancreatic Acinar Cell Carcinoma Growth Kinetics Are Independent of Dietary Vitamin D Deficiency or Supplementation - Dooley, James; Lagou, Vasiliki; Heirman, Nathalie; Dresselaers, Tom; Himmelreich, Uwe; Liston, Adrian (Frontiers in Oncology, 2017)
Vitamin D has been proposed as a therapeutic strategy in pancreatic cancer, yet evidence for an effect of dietary vitamin D on pancreatic cancer is ambiguous, with conflicting data from human epidemiological and intervention studies. Here we tested the role of dietary vitamin D in the in vivo context of the well-characterised Ela1-TAg transgenic mouse model of pancreatic acinar cell carcinoma. Through longitudinal magnetic resonance imaging of mice under conditions of either dietary vitamin D deficiency (<5 IU/kg vitamin D) or excess (76,500 IU/kg vitamin D), compared to control diet (1500 IU/kg vitamain D), we measured the effect of variation of dietary vitamin D on tumour kinetics. No measurable impact of dietary vitamin D was found on pancreatic acinar cell carcinoma development, growth or mortality, casting further doubt on the already equivocal data supporting potential therapeutic use in humans. The lack of any detectable effect of vitamin D, within the physiological range of dietary deficiency or supplementation, in this model further erodes confidence in vitamin D as an effective anti-tumour therapeutic in pancreatic acinar cell carcinoma.